Medical Causes of Death in Iranian Children Aged 1-59 Months: A Systematic Review and Meta-analysis - Gholamreza Mohammadi; Raheb Ghorbani; Shaqayegh Khosravifar; Masoudeh Babakhanian (Journal of Pediatrics Review)
Background: Preventing the years of life lost in newborns and children is one of the serious public health problems in underdeveloped countries. Objectives: This review aimed to highlight the significant determinants related to under-five child mortality in Iran (both in-hospital and out-of-hospital) through a systematic review of the literature. Methods: EMBASE, PubMed, Scopus, Magiran and Web of Science databases, as well as the Google Scholar search engine, were used for the systematic search of the literature for Iranian studies. Special syntax was used to search the relevant studies for the review. Original research articles in English and Persian until December 31, 2023, were included in the analysis and synthesis of the results. A total of 15 studies were incorporated into this review. Eligible articles were thoroughly appraised and pertinent information was extracted and integrated into the systematic review. Results: The highest frequency of mortality occurred in boys. The three most significant causes of death among Iranian children aged 1-59 months, respectively, are congenital disorders (28%), respiratory distress syndrome (18%) and non-traffic and traffic accidents (17%). Conclusions: The most common causes of mortality among Iranian children aged 1-59 include congenital abnormalities, unintentional injuries, mortality due to external factors, and respiratory infections. However, without accurate recording of causes of death using international classification of diseases 10th Revision (ICD-10), as well as conducting autopsy or registering precise age periods for children under five years old, it is not possible to adequately analyze extensive patterns of mortality in the country. Consequently, related public health planning is diminished, which negatively impacts efforts to effectively reduce mortality.